The dissemination of Palestinian news on facebook : a case study of Palestinian journalists - Muhaisen, Mohammed S. A. (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The purpose of this study is to explore the usage of Facebook among Palestinian journalists for dissemination of Palestinian news. The study focuses on Palestine news, from both Gaza Strip and West Bank, whereby these territories have witnessed rapid updates on daily life events through social media development. This study was directed by three research questions, which are: (1) How do Palestinian journalists frame Palestinian news on Facebook? (2) What is the rationale behind Palestinian journalists' decision in choosing Facebook to disseminate news to their followers? and (3) How significant is Facebook in changing the landscape of journalism practice in Palestine?. Framing Theory was employed in this study to investigate how Palestinian journalists frame the Palestinian news on Facebook. In order to answer the research questions, qualitative research method was adopted by conducting in-depth interviews with Palestinian journalists who are currently working in Palestine, own Facebook account and disseminate news through that social media platform. Data were collected through purposive sampling and later analysed using thematic analysis. It was found that Palestinian journalists frame their news posted on Facebook based on human interest frame, attribution of responsibility frame, morality frame, political frame, and public opinion frame. They use Facebook as a medium to disseminate the news because it is broadly used and popular, user-friendly and effective application, and allowing freedom of expression. The adoption of Facebook in the dissemination of news has changed the media landscape in Palestine by being a significant journalistic tool, increasing rapidity in news dissemination, becoming new source of information and encouraging two-way communication